2002
DOI: 10.1023/a:1015598228545
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Using the hydrophobic fluorescent dye 8-anilino-1-naphthalenesulfonic acid (8-ANS), a hydrophobic site on the surface of the protein globule of angiotensin-converting enzyme (ACE) from bovine lung was found. The dissociation constant of the ACE-8-ANS complex was estimated as 1.5 +/- 0.2 microM. This hydrophobic site is far from the ACE catalytic sites because the binding of the hydrophobic dye does not influence ACE activity. Shielding of the ACE hydrophobic site due to the complex formation with 8-ANS or Trit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Mutation of the highly conserved C loop ‐3 residue W594 resulted in perinatal death in vivo , and impaired trafficking and decreased activity for both domains in vitro (Michaud et al , 2014 ). In agreement with these studies, our analysis of motion correlation between protein cavities and docking of the 1,8‐ANS molecule, which is known to protect sACE against oxidative inactivation (Voronov et al , 2002 , 2003 ), showed that these three loops form the allosteric Site 1 which could regulate N‐domain activity. Further research is required to understand the intra‐ and interdomain cooperativity of different ligands, potentially via all‐atom MD simulations.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Mutation of the highly conserved C loop ‐3 residue W594 resulted in perinatal death in vivo , and impaired trafficking and decreased activity for both domains in vitro (Michaud et al , 2014 ). In agreement with these studies, our analysis of motion correlation between protein cavities and docking of the 1,8‐ANS molecule, which is known to protect sACE against oxidative inactivation (Voronov et al , 2002 , 2003 ), showed that these three loops form the allosteric Site 1 which could regulate N‐domain activity. Further research is required to understand the intra‐ and interdomain cooperativity of different ligands, potentially via all‐atom MD simulations.…”
Section: Discussionsupporting
confidence: 85%
“…Site 1 is hydrophobic and contains the only free N-domain cysteine residue C474 on C loop -2 (Fig 7A and B) which was identified by CovCys as a covalently targetable cysteine with 73% probability. Since cysteine residues are especially prone to oxidative inactivation (Huang et al, 2015) and it was previously shown that binding of the hydrophobic 1-anilinonaphthalene-8-sulfonic acid (1,8-ANS) dye could protect bovine sACE from rapid inactivation by gamma radiation-mediated water radiolysis (Voronov et al, 2002(Voronov et al, , 2003, we investigated whether this pocket could be the 1,8-ANS binding site. The 1,8-ANS molecule was blindly docked to the N-domain using EADock at the SwissDock server (Grosdidier et al, 2007) revealing the binding of top-ranking poses into allosteric Site 1 (Fig 7B and C), and substantiating our hypothesis that this surface pocket is important for catalytic activity.…”
Section: Monomeric Sace S1211 Undergoes Bending and Breathing Motionsmentioning
confidence: 99%
“…The new fabrication method of sensitive elements for gas sensors on the basis of the dielectric membrane structures is proposed and the group technology for manufacturing is developed. The main technological solution for the formation of such structures is the using of two-stage unilateral anisotropic etching of silicon [4]. It is necessary to carry out the final stage of anisotropic etching of silicon after the formation of sensitive layers with their protection against contact with etchant.…”
Section: Methodsmentioning
confidence: 99%
“…The suitability of the obtained films for fabrication of membrane structures was determined by dint of detecting mechanical stresses by visual control of the membrane bending during the direct heating to high temperature and extracting from heated etchant. Also the dielectric membrane films were examined for resistance to etching in the organic alkaline etchant for the final stage of anisotropic etching of silicon [4]. Mass fractions of the etchant components: diaminoethane : pyrocatechol : water = 55% : 20% : 25% (density of the etchant at 20 о С: ρ = 1,055 g/cm 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…The purpose of the work is search of optimum element composition of dielectric film for production of membrane structures (refer with: Fig. 1) by the method of the two-stage unilateral anisotropic etching of silicon, which feature is the formation of membranes at the final stage of anisotropic etching of silicon, after the formation of the sensitive layers, which demands their protection [4][5][6].…”
Section: Introductionmentioning
confidence: 99%